The perception of grassroots coaches of Spanish professional clubs on the process of training young players - Barrero, A. M.; Giménez Fuentes-Guerra, F. J.; Abad Robles, M. T. (Sports, 2022)
(1) The aims of this study were to find out the perception of the coaches of male and female football players in the initiation stage of Spanish professional clubs about different factors of the training process (context, talent development, and methodology), and to identify possible differences according to age/category (U10s: 8-10 years old, and U12s: 10-12 years old) and gender (male and female). (2) For this purpose, a questionnaire of 57 questions grouped into seven dimensions was applied, selecting for this work those related to talent development, training methodology, and social context. A total of 153 coaches from top-level Spanish professional clubs participated in the study: the first and second male division and the first female division. (3) The coaches consider that genetic inheritance is more important than contextual variables in the development of sporting talent. On the other hand, they do not show a clear consensus on whether players who perform better in the initiation stage have a greater chance of reaching the elite. (4) In addition, they value decision-making and technical qualities as fundamental factors in the development of talent rather than physical preparation.